Bio‐derived Carbon Nanofibres from Lignin as High‐Performance Li‐Ion Anode Materials. Issue 19 (12th September 2019) - Culebras, Mario; Geaney, Hugh; Beaucamp, Anne; Upadhyaya, Prathviraj; Dalton, Eric; Ryan, Kevin M.; Collins, Maurice N.
Abstract: Development of cost‐effective and increasingly efficient sustainable materials for energy‐storage devices, such Li‐ion batteries, is of crucial future importance. Herein, the preparation of carbon nanofibres from biopolymer blends of lignin (byproduct from the paper and pulp industry) and polylactic acid (PLA) or a thermoplastic elastomeric polyurethane (TPU) is described. SEM analysis shows the evolving microstructural morphology after each processing step (electrospinning, stabilisation and carbonisation). Importantly, it is possible to tailor the nanofibre porosity by utilising miscibility/immiscibility rules between lignin and the polymer additive (PLA/TPU). PLA blends (immiscible) generate porous structures whereas miscible lignin/TPU blends are solid when carbonised. Electrodes produced from 50 % PLA blends have capacity values of 611 mAh g −1 after 500 charge/discharge cycles, the highest reported to date for sustainable electrodes for Li‐ion batteries. Thus, this work will promote the development of lignocellulose waste materials as high‐performance energy‐storage materials. Abstract : Lignin anodes : The increasing demand for Li‐ion batteries it makes necessary to develop cost‐effective and energy‐efficient materials. The best way to achieve this is by utilising sustainable biobased materials. Lignin/polylactic acid (PLA) nanofibres show enormous potential owing their outstanding capacity values and satiability.